اتجاهات العلماء المعاصرين في الحجاب والاختلاط: دراسة مقارنة في ضوء نصوص القرآن والحديث - قزدر، محمد عامر (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research delves into those directives and injunctions in Surah al-Nur and Surah al-Ahzab that pertain to hijab and interaction between men and women. It focuses on a comparative study of the approaches of early and contemporary scholars in Islamic intellectual traditions. For this comparison, the study, in the light of related argumentations, also researches predominant assertions emanating from the discursiveness of discourses. The researcher probes into reasons for the difference of scholars in interpreting provisions of the issue and examines in depth the degrees of veracity and authenticity of ahadith of the Prophet (sws) they adduce in these contestations. In this regard, the researcher has used three approaches: The first is the inductive approach, which was appropriated in order to extract directives and injunctions regarding hijab and social interaction from Qur'anic text, gather significant inclinations that early and contemporary scholars had in this regard, and collected the prophetic traditions corpus on this issue. The second is a comparative one in which the approaches of early and contemporary scholars are compared and those deemed as preponderant are indicated after detailed discussion. The third is an analytical approach which focuses on the academic analysis of the viewpoints of scholars, critical study of Qur'anic exegeses, evaluation of available traditions and critical appreciation of their chain (sanad) and text (matan) according to the science of hadith. The researcher reached the following conclusions: All directives for social interaction between men and women in Surah al-Nur that relate to norms of comportment for one's gaze, care in dress to avoid sexual provocativeness, modesty in dress in general, exhibition of adornments and embellishment during social visits or other occasions of male-female interactions are for all times in Islamic sharia for Muslim men and women. As far as the directive of drawing over large cloaks required in Surah al-Ahzab is concerned, that is prescribed as a preventive measure for women when they go outside so as to safeguard themselves from mischief of rogues and scoundrels and to maintain their honor and dignity in unsafe situations. As far as those directives addressing wives of the Prophet (sws) are concerned, as in keeping themselves to their houses, withdrawing themselves from strangers, adopting complete hijab and avoiding the interaction with them, they were specific to wives of the Prophet (sws) and, in the light of textual foundations of the sharia and in consideration of social mores of Muslims in the times of the Prophet (sws) and the Rightly Guided Successors of his, it would certainly not be appropriate to generalize these directives for other, ordinary Muslim women.